2016
DOI: 10.1128/iai.00496-16
|View full text |Cite
|
Sign up to set email alerts
|

Filifactor alocis Promotes Neutrophil Degranulation and Chemotactic Activity

Abstract: Filifactor alocis is a recently recognized periodontal pathogen; however, little is known regarding its interactions with the immune system. As the first-responder phagocytic cells, neutrophils are recruited in large numbers to the periodontal pocket, where they play a crucial role in the innate defense of the periodontium. Thus, in order to colonize, successful periodontal pathogens must devise means to interfere with neutrophil chemotaxis and activation. In this study, we assessed major neutrophil functions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 60 publications
8
49
0
1
Order By: Relevance
“…8A and B). Similar to the response we described with non-opsonized F. alocis (Armstrong, Miralda, Neff, Tian, Vashishta, Perez, … Uriarte, 2016); serum opsonized F. alocis significantly induced secretory vesicles and specific granule exocytosis (Fig. 8A and B).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…8A and B). Similar to the response we described with non-opsonized F. alocis (Armstrong, Miralda, Neff, Tian, Vashishta, Perez, … Uriarte, 2016); serum opsonized F. alocis significantly induced secretory vesicles and specific granule exocytosis (Fig. 8A and B).…”
Section: Resultssupporting
confidence: 86%
“…We recently described that non-opsonized F. alocis , through TLR2 activation, promotes exocytosis of secretory vesicles and specific granules but not azurophil granules in human neutrophils; as well as enhanced random and directed migration (Armstrong, Miralda, Neff, Tian, Vashishta, Perez,… Uriarte, 2016). We next examined if opsonized HK F. alocis would induce a similar or distinct granule exocytosis pattern compared to the live organism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, F. nucleatum, P. gingivalis, and T. denticola can induce the release of elastase from neutrophils, and Aggregatibacter actinomycetemcomitans can induce MPO release (40,51,52). In contrast, we recently showed that the newly recognized periodontal pathogen Filifactor alocis did not induce azurophil granule release even at a high multiplicity of infection (53). Hence, various neutrophil responses may contribute to the pathogenic potential of different pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 80%
“…Neutrophils recognize F. alocis through TLR2, which triggers degranulation and cell migration (325 saw that PAM3CSK4 induced priming in only certain neutrophil donor populations, however FSL-1 induced priming in neutrophils from all of our donor pool (Fig. 3-4 A-B).…”
Section: Resultsmentioning
confidence: 99%